2019
DOI: 10.1021/acsomega.8b03619
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Second Hyperpolarizabilities of Intramolecular Pancake-Bonded Diradicaloids with Helical Scaffolds

Abstract: Using the spin-unrestricted density functional theory method, we have investigated a novel class of open-shell singlet fused-ring molecules with helical scaffolds toward the development of highly efficient third-order nonlinear optical (NLO) systems. It turns out that the helical molecules possess pancake bonding with intermediate diradical character and thereby exhibit large enhancement of orientationally-averaged second hyperpolarizability γ s values (third-order NLO properties at the molecular scale) as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The Romberg-Rutishauer method [54][55][56] has been employed in order to safeguard the numerical stability of the computed (hyper)polarizability values. The computed static (hyper)polarizability values are expected to be useful for a relative comparison of the NLO properties of the studied photoswitchable compounds, since these are a good approximation of dynamic ones (frequency-dependent) in the off-resonant region [57]. The following field strengths have been used: 2 m F, m = 1-4, and F = 0.0005 a.u.…”
Section: Definitionsmentioning
confidence: 99%
“…The Romberg-Rutishauer method [54][55][56] has been employed in order to safeguard the numerical stability of the computed (hyper)polarizability values. The computed static (hyper)polarizability values are expected to be useful for a relative comparison of the NLO properties of the studied photoswitchable compounds, since these are a good approximation of dynamic ones (frequency-dependent) in the off-resonant region [57]. The following field strengths have been used: 2 m F, m = 1-4, and F = 0.0005 a.u.…”
Section: Definitionsmentioning
confidence: 99%
“…In the past decades, open-shell polycyclic aromatic hydrocarbons (PAHs), in particular diradicals (diradicaloids), have attracted considerable attention of researchers due to their unusual magnetic , and nonlinear optical properties as well as the capabilities to manifest singlet fission. Low singlet–triplet energy difference of biradicaloid compounds promotes exhibiting semiconductor characteristics, which can be enhanced by the formation of intermolecular polycentric “pancake bonds”. The above-mentioned features make PAHs a promising base of new materials for organic electronics, quantum information processing systems, lithium-ion batteries, nonlinear optics, and spintronics. This type of compound includes zigzag PAHs–zethrenes, in which two phenalenyl moieties are linked head-to-head with or without an acene linker. Zethrenes studied to date, depending on the number of benzene rings ( n = 1–3) in the central fragment of the molecule, can exist in biradicaloid state or at least demonstrate coexistence of two resonant forms. The first one represents a structure with quinoidal form of the linker ensuring closed electronic shell of the compound (closed shell singlet, CSS), while the second one is characterized by an aromatic linker and comprises two paramagnetic centers, antiferromagnetic exchange interactions between which stabilize the system in the singlet state (open shell singlet, OSS) (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that the tunability of the DRC represents a fruitful computational approach for the discovery of new organic materials [4][5][6][7][8]. For example, molecules with a moderate (0.5) diradical character, i.e., diradicaloids, possess unusually high values of the second hyperpolarizability and are attractive for application in organic photonics [9][10][11][12]. It was also shown that compounds with a low-to-intermediate (0.1-0.5) diradical character are potential singlet fission materials [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%